2004
DOI: 10.1158/1078-0432.ccr-04-0392
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island Hypermethylation of the DNA Repair Enzyme Methyltransferase Predicts Response to Temozolomide in Primary Gliomas

Abstract: Purpose: The DNA repair enzyme O 6 -methylguanine DNA methyltransferase (MGMT) inhibits the killing of tumor cells by alkylating agents, and its loss in cancer cells is associated with hypermethylation of the MGMT CpG island. Thus, methylation of MGMT has been correlated with the clinical response to 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) in primary gliomas. Here, we investigate whether the presence of MGMT methylation in gliomas is also a good predictor of response to another emergent alkylating agent, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(149 citation statements)
references
References 36 publications
11
131
2
1
Order By: Relevance
“…Quite low amounts are expressed in brain tumours (Chen et al, 1992;Preuss et al, 1995;Silber et al, 1999;Bobola et al, 2001), presumably due to MGMT promoter methylation (Esteller et al, 1999(Esteller et al, , 2001. MGMT expression level (Chen et al, 1999;Anda et al, 2003) and, as recently shown, MGMT promoter methylation (Esteller et al, 2000;Hegi et al, 2004Hegi et al, , 2005Paz et al, 2004) were predictive for the clinical response to chemotherapy, stressing the critical role of MGMT in determining alkylating drug resistance (for a review see Gerson, 2004). Brain tumours, notably malignant gliomas, are highly therapy-refractory tumours.…”
Section: Introductionmentioning
confidence: 89%
“…Quite low amounts are expressed in brain tumours (Chen et al, 1992;Preuss et al, 1995;Silber et al, 1999;Bobola et al, 2001), presumably due to MGMT promoter methylation (Esteller et al, 1999(Esteller et al, , 2001. MGMT expression level (Chen et al, 1999;Anda et al, 2003) and, as recently shown, MGMT promoter methylation (Esteller et al, 2000;Hegi et al, 2004Hegi et al, , 2005Paz et al, 2004) were predictive for the clinical response to chemotherapy, stressing the critical role of MGMT in determining alkylating drug resistance (for a review see Gerson, 2004). Brain tumours, notably malignant gliomas, are highly therapy-refractory tumours.…”
Section: Introductionmentioning
confidence: 89%
“…Although not being subjected to mutations, MGMT downregulation due to promoter methylation has been shown to predict response to temozolomide, but not to temozolomide in concert with cisplatinum in patients with high-grade gliomas or glioblastomas. 278,279 The hypothesis that low levels of MGMT predict temozolomide efficacy is further supported by a study revealing improved survival related to MGMT methylation in glioblastoma patients receiving temozolomide therapy, 280 although in this case study design do not allow a distinction between prediction and prognostication (effect of biology independent of specific therapy).…”
Section: Mismatch Repairmentioning
confidence: 99%
“…As a result, it inhibits the killing of tumour cells by alkylating agents. Hypermethylation of the MGMT promoter and associated loss of expression correlates with response to temozolamide and BCNU in primary gliomas (Esteller et al, 2000;Paz et al, 2004) and is an independent predictor of overall and progression-free survival in patients with diffuse large B-cell lymphoma treated with cyclophosphamide-containing regimens . Importantly, the methylation status of MGMT in gliomas at presentation does not correlate with the clinical response when temozolamide is used at relapse, demonstrating that the value of biomarkers may depend on when during tumour progression or treatment they are measured.…”
Section: Evidence For the Role Of Epigenetic Mechanisms In Drug Resismentioning
confidence: 99%